2016
DOI: 10.3233/jnd-160147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Profile of Duchene and Becker Muscular Dystrophy in Puerto Rico

Abstract: Background Duchenne and Becker Muscular Dystrophy (DMD and BMD, respectively), are common forms of inherited muscle disease. Information regarding the epidemiology of these conditions, including genotype, is still sparse. Objective To establish the prevalence and genetic profile of DMD and BMD in Puerto Rico. Methods We collected data from medical records in all Muscular Dystrophy Association (MDA) clinics in Puerto Rico in order to estimate the prevalence of DMD and BMD and to describe the genotypic profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Second, we also confirmed findings from other studies that demonstrate racial/ethnic differences in DBMD prevalence [10-27, 33]. For example, a South African study with 143 DMD patients diagnosed during 1987–1992 found substantial variation in DMD minimum prevalence (per 10,000) in blacks of 0.04 compared to 0.12 for whites, 0.71 for Indians, and 0.22 for mixed ancestry [10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, we also confirmed findings from other studies that demonstrate racial/ethnic differences in DBMD prevalence [10-27, 33]. For example, a South African study with 143 DMD patients diagnosed during 1987–1992 found substantial variation in DMD minimum prevalence (per 10,000) in blacks of 0.04 compared to 0.12 for whites, 0.71 for Indians, and 0.22 for mixed ancestry [10].…”
Section: Discussionsupporting
confidence: 89%
“…Studies from European countries, where whites are the majority, have reported DMD prevalence ranges from 0.20 to –2.50 [11, 13-15, 17, 18, 22-26]. A study in Puerto Rico, where Hispanics are the majority, found that the minimum prevalence for all age groups was 0.8 per 10,000 males in 2012 [33]. Our new findings are in line with the previous analysis of MD STAR net data, but with 32.1% new cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 317 patients with DMD/BMD from southern India showed that the most frequent deletion was in exons 45–47 (Vengalil et al, ). Deletion of exons 45–47 was also the most frequently occurring pattern in 141 patients with DMD/BMD from Puerto Rico (Ramos et al, ). In 180 Polish patients with DMD/BMD, the deletion mainly involved exons 45–54 and exons 3–21 (Zimowski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 22 studies reporting DMD prevalence, 13 (59.1%) were European [25, 27, 30, 31, 33-37, 39, 41, 43, 46], 4 (18.2%) American [26,42,44,45], 2 (9.1%) Asian [29,38] and 3 (13.6%) were African [32,40].…”
Section: Pooled Dmd Overall and Birth Prevalencementioning
confidence: 99%